2019
DOI: 10.1371/journal.pgen.1007991
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of DNA-bound transcription factor Sko1 prevents its association with nontarget promoters

Abstract: Sequence-specific transcription factors (TFs) represent one of the largest groups of proteins that is targeted for SUMO post-translational modification, in both yeast and humans. SUMO modification can have diverse effects, but recent studies showed that sumoylation reduces the interaction of multiple TFs with DNA in living cells. Whether this relates to a general role for sumoylation in TF binding site selection, however, has not been fully explored because few genome-wide studies aimed at studying such a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…Extending our previous work on Gcn4 and Sko1, we have now shown that another bZIP transcription factor, Cst6, is also regulated by sumoylation in budding yeast (Rosonina et al 2012;Sri Theivakadadcham et al 2019). Gcn4 expression (and consequently, its sumoylation) is dependent on amino acid starvation, but like Sko1, a fraction of Cst6 molecules is sumoylated during normal growth conditions, suggesting that the modification regulates properties of the transcription factor not related to stress.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Extending our previous work on Gcn4 and Sko1, we have now shown that another bZIP transcription factor, Cst6, is also regulated by sumoylation in budding yeast (Rosonina et al 2012;Sri Theivakadadcham et al 2019). Gcn4 expression (and consequently, its sumoylation) is dependent on amino acid starvation, but like Sko1, a fraction of Cst6 molecules is sumoylated during normal growth conditions, suggesting that the modification regulates properties of the transcription factor not related to stress.…”
Section: Discussionsupporting
confidence: 77%
“…For some transcription factors, sumoylation was shown to occur specifically after they bind to target promoters and the modification facilitates their subsequent removal from DNA, thereby enabling gene deactivation or restricting expression levels (e.g. Gcn4, Ikaros, and Sko1; (Rosonina et al 2012;Apostolov et al 2016;Sri Theivakadadcham et al 2019)). As mentioned above, however, in other cases, sumoylation promotes the interaction of transcription factors with DNA (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations